IS HER DIAGNOSIS MAJOR DEPRESSION OR SEXUAL REPRESSION?: A NON-WESTERN FIJIAN FEMALE CLINICAL SINGLE CASE STUDY - Leo Marai (Faculty of Psychology, Universitas Gadjah Mada, 1999)
This article presents a case of a 25-year-old non-western Fijian working class woman who became severely depressed following a love relationship problem. During six months of cognitive-behavioral treatment involving two 1 hour weekly session specifically applying Beck, Rush, Shaw, and Emery (1979) standard cognitive therapy resulted in no treatment gain. This indicates the inefficacy of such intervention, thus being attributed to differential clinical diagnosis of the syndrome. After termination of therapy, a further in-dept case analysis and review of the patient revealed the importance of sexual repression as possible underlying syndrome, thus suggesting Freud’s psychoanalytic conceptualization of this problem as a possible explanation of her many depressive and anxious symptoms. A prospective suggestion on possible psychoanalytic treatment is advocated for in such future case of similar nature. The problems of classification of mental disorders in Diagnostic Statistical Manual (DSM), clinical diagnosis, clinical judgment, and therapeutic bias, are briefly highlighted and discussed with some concluding suggestions. Keywords: Diagnosis Major Depression or Sexual Repression